Three sympatric karyomorphs in the fish Astyanax fasciatus (Teleostei, Characidae) do not seem to hybridize in natural populations - Ferreira-Neto, Maressa [UNESP]; Artoni, Roberto Ferreira; Vicari, Marcelo Ricardo; Moreira-Filho, Orlando; Martinez Camacho, Juan Pedro; Bakkali, Mohammed; de Oliveira, Claudio [UNESP]; Foresti, Fausto [UNESP] (Zoological Inst, 2012)
Ninety individuals of the characid fish Astyanax fasciatus (Cuvier, 1819) were collected at Agua da Madalena stream (Botucatu, São Paulo, Brazil) and analyzed for diploid chromosome number 2n and karyotype composition as well as for the chromosomal location of the 5S and 18S ribosomal DNA (rDNA). Whereas no chromosome differences were associated with sex, three different karyomorphs with diploid chromosome numbers 2n=46, 2n=48 and 2n=50 were found. No intermediate 2n numbers were discovered. The 2n=50 karyomorph showed some differences in 18S rDNA location compared to the two other karyomorphs. Finally, all specimens with the 2n=46 karyomorph showed the presence of a partly heterochromatic macro supernumerary chromosome, which was absent in all individuals with the two other karyomorphs. All these results suggest that indviduals of the three different karyomorphs are not likely to hybridize in the examined populations. Our findings strongly suggest the presence of three separate species (sensu biological species concept) easily diagnosed on the basis of differences in the diploid chromosome numbers and other chromosomal markers.
Keywords: fish cytogenetics; chromosome banding; rDNA; sympatric differentiation; B chromosome